2016
DOI: 10.1007/s10877-016-9951-4
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of stroke volume variation in patients of a general intensive care unit: a longitudinal observational study

Abstract: Sinus rhythm (SR) and controlled mechanical ventilation (CV) are mandatory for the applicability of respiratory changes of the arterial curve such as stroke volume variation (SVV) to predict fluid-responsiveness. Furthermore, several secondary limitations including tidal volumes <8 mL/kg and SVV-values within the "gray zone" of 9-13% impair prediction of fluid-responsiveness by SVV. Therefore, we investigated the prevalence of these four conditions in general ICU-patients. This longitudinal observational study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 52 publications
1
18
0
Order By: Relevance
“…The concept of assessing fluid responsiveness was initially adopted in patients receiving mechanical ventilation, without spontaneous breathing, with a tidal volume exceeding 7 mL/kg, and a regular heart rate rhythm. These criteria are not applicable to about 90% of patients in the intensive care unit, which therefore limits the use of dynamic indices in the peri‐operative period . Previous studies have reported that various interventions improved the reliability of dynamic indices even in patients with low tidal volume ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The concept of assessing fluid responsiveness was initially adopted in patients receiving mechanical ventilation, without spontaneous breathing, with a tidal volume exceeding 7 mL/kg, and a regular heart rate rhythm. These criteria are not applicable to about 90% of patients in the intensive care unit, which therefore limits the use of dynamic indices in the peri‐operative period . Previous studies have reported that various interventions improved the reliability of dynamic indices even in patients with low tidal volume ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…These criteria are not applicable to about 90% of patients in the intensive care unit, which therefore limits the use of dynamic indices in the peri-operative period. 8 19 However, these studies were conducted in mechanically ventilated patients. In particular, the presence of spontaneous breathing is considered to be a major limitation to the application of dynamic indices, which have clinically unacceptable reliability in patients with spontaneous breathing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, certain conditions, including arrhythmias and spontaneous breathing, impose some limitations for the clinical use of dynamic indices [14]. In particular, these indices have poor predictability for fluid responsiveness in patients with low tidal volumes (< 8 ml/kg) or low driving airway pressures (< 20 cm H 2 O) [15,16].…”
Section: Introductionmentioning
confidence: 99%